Development and Application of Ultra High Strength Cable forDeep Ten Thousand Meter Wells - MA Jianghu; ZHANG Bingjun; ZHANG Haijun; YANG Qingjian; SHUAI Shichen; LUO Shengqiang; YOU Zhanhua; SUN Wei; JIANG Songhan (Cejing jishu)
In response to the challenges of high tension and ultra long signal transmission faced by cable logging in deep 10 000-meter wells, this article adopts a combination of theoretical design, data analysis, and experimental testing. By redesigning the chemical composition of steel and optimizing the steel wire processing technology, the cable breaking force is improved. By optimizing the design of the cable core structure, increasing the diameter of the cable core conductor and the thickness of the insulation layer, reducing the impedance and capacitance parameters of the cable, and improving the long-distance communication performance of the cable, an ultra high strength cable suitable for deep 10 000-meter well logging has been developed. To ensure its performance, cable mechanical performance testing, communication performance testing, and corrosion resistance testing are conducted in sequence. The testing results showed that the cable has high reliability and adaptability, meeting the requirements of deep well logging operations. Ultra-high strength cables have been used in multiple practical applications in the deep well blocks of Tarim oilfield and Southwest oil and gas field, successfully completing the deep CKX well four opening logging task with good application results, laying a solid foundation for the logging of over 10 000-meters of cables.